The battle over broadcast regulation: can the free press survive a free market approach? - Jackson, Pamela Taylor, author; Stanfield, J. Ron, advisor (Colorado State University. Libraries, 2008)
This dissertation examines the 100-year-old political economic evolution of broadcast regulation in the U.S., primarily focusing on the shift toward a free market approach to FCC policy decisions and the consequences for a free press in democratic society. Deregulation and concentration of media ownership trends have cast doubt on the independence of the press, and raised questions regarding the vitality and viability of American democracy. This research is premised on the belief that an effective democracy cannot exist without an informed public, and voters rely on the news media for the knowledge they need to make accurate social valuations in the political process. Evidence suggests the important mission of a free press to keep the citizenry informed is being derailed by institutional and market failures. Immediate institutional and regulatory reforms are recommended to insulate the press from the predatory expansion of a free market system that permeates every aspect of social life, including broadcast regulation and policy. The profit values of a market system clash and interfere with the moral agency of a free press, and the two are inherently incompatible. In addition, this study concludes that the growing Internet-based grassroots media reform movement in the U.S. is the last best hope for driving a corrective response to reverse the damage already done to the institution of news and to reinstate the news media's role as public interest advocates in a democracy. A multi-disciplinary approach is adopted to chart the evolution of broadcast regulation since the early 1900s and the fallout for a free press in democratic society. A broad spectrum survey of economics, political science, and mass communications literature allows for a synthesis of otherwise divergent theoretical perspectives in examining the free press-free market paradox. The theories addressed include institutional change, comparative economic systems as applied to changing budget constraints for network news divisions, commodification theory, regulatory capture, political ideology, democratic thought, market-driven journalism, and the propaganda model of news production. In particular, this research offers an unprecedented application of commodification theory and economic transition theory to the problem of the sustainability of a free press.
Keywords: broadcast regulation; broadcast regulation and policy; free market; media consolidation; media democracy; media economics; network news; news; news production; press; journalism; political science